1998
DOI: 10.1021/jp982111e
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Studies of Hydrogen Peroxide in Solid Rare Gases:  Formation of the HOH···O(3P) Complex

Abstract: UV photolysis of H2O2 in solid Ar, Kr, and Xe yields isolated OH radicals and a complex between a water molecule and a ground-state (3P) oxygen atom. The vibrational bands of the HOH···O complex are observed at 3730.1 and 3633.0 cm-1 in Ar, at 3718.6 and 3622.4 cm-1 in Kr, and at 3704.3 and 3607.3 cm-1 in Xe matrices. The assignment is based on isotopic substitution, selective photoinduced processes between H2O2 and HOH···O, and ab initio calculations. In Kr and Xe matrices, the complex is formed with much les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
90
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(101 citation statements)
references
References 47 publications
(67 reference statements)
10
90
1
Order By: Relevance
“…[34] This complex has been studied by IR spectroscopy combined with quantum chemical calculations at the MP2 level in various basis sets up to 6-311 + + G(3d,3p). [35] The quantum chemical calculations performed at the UMP2/ 6-311 + + G(3d,3p) level confirmed the structure and the assignment of IR absorption bands proposed on the basis of the experimental study. The optimized geometry of the complex corresponds to the open hydrogen-bonded bent structure shown in Figure 3.…”
Section: Complexes Of H 2 O With Atomic Oxygensupporting
confidence: 66%
See 2 more Smart Citations
“…[34] This complex has been studied by IR spectroscopy combined with quantum chemical calculations at the MP2 level in various basis sets up to 6-311 + + G(3d,3p). [35] The quantum chemical calculations performed at the UMP2/ 6-311 + + G(3d,3p) level confirmed the structure and the assignment of IR absorption bands proposed on the basis of the experimental study. The optimized geometry of the complex corresponds to the open hydrogen-bonded bent structure shown in Figure 3.…”
Section: Complexes Of H 2 O With Atomic Oxygensupporting
confidence: 66%
“…This process has been investigated in detail in matrix isolation studies and quantum chemical calculations. [34,35] It was found that the HOC radicals formed from the photolysis of H 2 O 2 (under 193 nm laser irradiation) in an argon matrix form a hydrogen-bonded complex between a water molecule and a triplet oxygen atom HÀOÀH···O( 3 P) in high (80 %) yield. [34] This complex has been studied by IR spectroscopy combined with quantum chemical calculations at the MP2 level in various basis sets up to 6-311 + + G(3d,3p).…”
Section: Complexes Of H 2 O With Atomic Oxygenmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that the hydrogen bonded complex to the oxygen atom HOHÁ Á ÁO( 3 P) was detected in low temperature matrices by Pehkonen et al 36 Recently, Cozzarín et al 37 reported the formation of the OCÁ Á ÁS complex after irradiation of OCS/Ar matrices. To the best of our knowledge the SÁ Á ÁHCN complex observed here is the second molecular complex with atomic sulfur ( 3 P) detected experimentally, and the first being of the hydrogen bond type.…”
Section: Resultsmentioning
confidence: 98%
“…10 Matrix-isolation infrared (IR) spectroscopy has been shown to be a powerful method to study intermolecular interactions, including those with phenol. [17][18][19][20][21][22][23][24][25] The early studies of self-association of phenol in argon and nitrogen matrices yielded the characteristic OH stretching bands of phenol monomer, dimer, and some multimers. 22 The recent experiments in argon matrices have indicated the formation of the H-bonded phenol dimer and phenol· · ·H 2 O complex.…”
Section: Introductionmentioning
confidence: 99%